Siasat Kompasiana dan Indonesiana dalam Memanfaatkan Raksasa Media Sosial Demi Traffic - Aryo Subarkah Eddyono (Jurnal Komunikasi, 2019)
The presence of giant social media (Facebook, Twitter, YouTube, and Instagram) does not necessarily make the mass media afraid and relent without doing anything. The purpose of this study is to answer  how are Kompasiana and Indonesiana, media that accommodate content originating from citizens with social media format, in using giant social media? The data were obtained from interviews with the managers of Kompasiana and Indonesiana, observations, documents, and various literatures. The results of this study are, Kompasiana and Indonesiana use giant social media to disseminate content, including promotion or campaign activities; used to increase engagement with members (user account) and the public; used to overcome technological limitations (answering blog video trends); and social media used to discuss issues to determine content policy. The use of the social media giant by Kompasiana and Indonesiana aims at increasing traffic to attract sponsors to advertise. This is important for Kompasiana and Indonesiana to survive and get benefit (capital). This study also shows that in the midst of domination efforts, subordinate groups will always try to get opportunities to survive. Keywords: Social Media, Kompasiana, Indonesiana, Capital, Traffic